Tumor de células de la granulosa en ovario de perra Bulldog Inglés (2023)
Clinical findings regarding ovarian tumors in canines are poorly documented, that is why it is estimated that its true prevalence is unknown since the literature reports that can be found are based on incidental cases or autopsies. It is likely that the incidence of these cases is higher due to the lack of reports to date. This report describes the clinical case of a patient, a 7-year-old female English bulldog, that was brought to consult with serosanguineous vulvovaginal discharge of several weeks of evolution, previously treated for two weeks with antibiotic therapy with no improvement.